Characterisation of the performance of single point diamond dressers in abrasive processes - Murphy, Stuart (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
This thesis presents in-depth investigation and analysis of the dressing of conventional grinding wheels. Grinding is used in the manufacturing industry to achieve a high surface finish which is an important constituent of the overall productivity. Although the desired surface quality of a product is dependent on the functional requirements of the product, the surface finish itself is dependent on the process characteristics of the grinding process. One of the most important parameters that determine the workpiece surface finish is the dressing process as it has a direct impact on the topography of the wheel.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin